2013
DOI: 10.1021/bm400327a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interactions between Grafted Hyaluronic Acid and Lubricin Provide Enhanced Wear Protection and Lubrication

Abstract: Normal (e.g., adhesion) and lateral (friction) forces were measured between physisorbed and chemically grafted layers of hyaluronic acid (HA), an anionic polyelectrolyte in the presence of lubricin (Lub), a mucinous glycoprotein, on mica surfaces using a surface forces apparatus (SFA). This work demonstrates that high friction coefficients between the surfaces do not necessarily correlate with surface damage and that chemically grafted HA acts synergistically with Lub to provide friction reduction and enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
186
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(200 citation statements)
references
References 41 publications
10
186
1
3
Order By: Relevance
“…This idea is in agreement with previous studies reporting that both wear protection and friction forces are highly sensitive to LUB concentration. 18,26,43 Although they exhibited the highest friction coefficients among all tribosystems studied, FN+ESF films provided effective wear protection of surfaces (similar to that observed for FN+LUB films). This finding reaffirms that coefficients of friction and wear protection are not necessarily related to each other.…”
Section: ■ Discussionsupporting
confidence: 57%
“…This idea is in agreement with previous studies reporting that both wear protection and friction forces are highly sensitive to LUB concentration. 18,26,43 Although they exhibited the highest friction coefficients among all tribosystems studied, FN+ESF films provided effective wear protection of surfaces (similar to that observed for FN+LUB films). This finding reaffirms that coefficients of friction and wear protection are not necessarily related to each other.…”
Section: ■ Discussionsupporting
confidence: 57%
“…Our studies clearly identify EGFR signaling as an important pathway that promotes the production of Prg4 at the cartilage surface. Many studies suggest a synergistic interaction between Prg4 and HA to promote more effective boundary lubrication (21)(22)(23). Interestingly, our data reveal that both lubricants are remarkably decreased in EGFR-deficient joints.…”
Section: Discussionmentioning
confidence: 50%
“…to compensate for lubricin loss. Recent studies have indicated that hyaluronan acts synergistically with lubricin to provide friction reduction and greater wear protection in certain experimental conditions (Das et al, 2013). Our study would suggest that increased Has2 expression is not sufficient to prevent the articular cartilage damage and dysfunction seen in Prg4 mutant mice.…”
Section: Discussionmentioning
confidence: 64%